Preços de transferência e margens de lucro alternativas - Balsimelli, Felipe Cerrutti (2016)
The present study analyzes the Brazilian transfer pricing rules, regarding the possible use of advanced price agreements (APAs). The Brazilian APAs has grounds on the proper Brazilian legislation: Law No. 9430/1996, Normative Ruling No. 1312/2012, Ordinance No. 222/2008 and other applicable Brazilian rules. This study presents the APAs as viable instruments to achieve the arm’s length principle and to avoid the distortions caused by the Brazilian fixed margin methods: PRL, CPL, CAP, PVA and PVV, in spite of its practicability. Although not expressly set forth in the Brazilian Federal Constitution of 1988 (FC/88), nor in the domestic Brazilian transfer pricing legislation (which was inspired in the OECD model), the arm’s length principle is presented as a proper 'Brazilian principle'. In this sense, the Brazilian arm’s length principle is presented within the context of other effective Brazilian tax principles expressly provided in the FC/88: mainly the constitutional principles of equality, contributive capacity, legality and mandatorily administrative act. According to the arm’s length principle, based on which transactions between related parties should equalized to the ones carried out by independent parties, the Brazilian transfer pricing rules are defended as constitutional rules, provided the alternative margins are feasible from a legal and practical perspective. This study concludes that the Brazilian APAs are legal and practical instruments to avoid administrative and judicial disputes, as well as to achieve the transfer pricing adjustments at real arm’s length conditions. It also exams the nature of Brazilian APAs (formal consultations) and provides a practice guidance for its application, as well as a critic overview of the applicable legislation.